Merkel cell polyomavirus DNA sequences in the buffy coats of healthy blood donors. - Pancaldi, Cecilia; Corazzari, Valentina; Maniero, Stefania; Mazzoni, Elisa; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Blood, 2011)
Merkel cell polyomavirus (MCPyV), a DNA tumor virus, has been found to be associated with Merkel cell carcinoma and chronic lymphocytic leukemia. MCPyV sequences have also been detected in various normal tissues in tumor-affected patients. Immunologic studies have detected MCPyV antibodies in as many as 80% of healthy blood donors. This high seroprevalence suggests that MCPyV infection is widespread in humans. In our study, buffy coats, which were examined for MCPyV DNA Tag sequences, showed a prevalence of 22%. Viral DNA load was revealed in blood samples from 10 to 100 molecules/100 000 cells. DNA sequencing confirmed that polymerase chain reaction amplicons belong to the MCPyV strain, MKL-1. To interpret the putative role of MCPyV in chronic lymphocytic leukemia, we may infer that, during a long period of viral persistence in blood cells, this DNA tumor virus may generate mutants, which are able to participate as cofactors in the multistep process of cell transformation.
Keywords: Adult; Aged; Base Sequence; Blood Buffy Coat; Carcinoma, Merkel Cell; Databases, Nucleic Acid; DNA, Viral; Expressed Sequence Tags; Humans; Italy; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Analysis, DNA; Tumor Virus Infections; Viral Load; Young Adult